Experimental Measurements of Mechanical Properties of PUR Foam Used for Testing Medical Devices and Instruments Depending on Temperature, Density and Strain Rate - Horak, Zdenek; Dvorak, Karel; Zarybnicka, Lucie; Vojackova, Hana; Dvorakova, Jana; Vilimek, Miloslav (Materials (Basel, Switzerland), 2020)
Rigid polyurethane (PUR) foam is products used as a biomedical material for medical device testing. Thermal stability is a very important parameter for evaluating the feasibility of use for testing surgical instrument load during drilling. This work aimed to perform experimental measurements to determine the dependence of the mechanical properties of a certified PUR on temperature, strain rate and density. Experimental measurements were realised for three types of the PUR samples with different density 10, 25 and 40 pounds per cubic foot. The samples were characterised in terms of their mechanical properties evaluated from tensile and compression tests at temperatures of 25 °C, 90 °C and 155 °C. Furthermore, the structures of the samples were characterised using optical microscope, their thermal properties were characterised by thermogravimetric analysis, and their density and stiffness with the effect of temperature was monitored. The results show that it is optimal not only for mechanical testing but also for testing surgical instruments that generate heat during machining. On the basis of experimental measurements and evaluations of the obtained values, the tested materials are suitable for mechanical testing of medical devices. At the same time, this material is also suitable for testing surgical instruments that generate heat during machining.
Keywords: polyurethane foam; rigid polyurethane foam; mechanical properties; thermal loading; temperature